Clinicodemographic profile and treatment outcome in patients of ocular surface squamous neoplasia - Meel, Rachna (Indian J Ophthalmol, 2017)
PURPOSE: The aim is to study the clinicodemographic profile and treatment outcome of ocular surface squamous neoplasia (OSSN). METHODS: This was a retrospective observational study of 57 eyes (56 cases) with clinically diagnosed OSSN, presenting in our center over the past year. RESULTS: The median age of presentation was 55 years with male:female ratio being 4.5:1. Systemic predisposing conditions were xeroderma pigmentosa (1) postkidney transplant immunosuppression (1), and human immunodeficiency virus infection (1). Patients with predisposing conditions had a younger median age of onset (33 years). The majority of tumors were nodular (61.4%), gelatinous (61.4%), and had limbal involvement (96%). On ultrasound biomicroscopy (UBM), mean tumor height was 2.93 ± 1.02 mm, and intraocular extension was evident in seven eyes. OSSN with intraocular extension had a mean tumor height of 4.3 ± 1.32 mm. Nodal metastasis was seen in one case at presentation. As per American Joint Committee for Cancer Classification seventh edition staging-two cases were T1, one was T2, 46 were T3 and eight were T4. Treatment advised included conservative therapy for 39; wide local excision (4 mm margin clearance) with cryotherapy for seven; enucleation in four; and exenteration in four eyes. Overall, complete regression was achieved in 88% of cases during a mean follow-up of 13.5 ± 4.6 months. Recurrence was seen in three cases, which were treated with exenteration, radical neck dissection, and palliative chemo-radiotherapy, respectively. CONCLUSION: Although associated with old age, earlier onset of OSSN is seen in patients with systemic predisposing conditions. Thicker tumors in the setting of a previous surgery or immunocompromised status should be considered high-risk features for intraocular extension and should be evaluated on UBM.